Determinants of Shoot Biomass Production in Mulberry: Combined Selection with Leaf Morphological and Physiological Traits - Cao, Xu (Plants (Basel), 2019)
Physiological and morphological traits have a considerable impact on the biomass production of fast-growing trees. To compare cultivar difference in shoot biomass and investigate its relationships with leaf functional traits in mulberry, agronomic traits and 20 physiological and morphological attributes of 3-year-old mulberry trees from eight cultivars growing in a common garden were analyzed. The cultivars Xiang7920, Yu711, and Yunsang2 had higher shoot fresh biomass (SFB), which was closely associated with their rapid leaf expansion rate, large leaf area, and high stable carbon isotope composition (δ(13)C). Conversely, the cultivars 7307, Husang32, Wupu, Yunguo1, and Liaolu11 were less productive, and this was primarily the result of slower leaf expansion and smaller leaf size. Growth performance was negatively correlated with leaf δ(13)C and positively correlated with the total nitrogen concentration, indicating that a compromise exists in mulberry between water use efficiency (WUE) (low δ(13)C) and high nitrogen consumption for rapid growth. Several morphological traits, including the maximum leaf area (LA(max)), leaf width and length, petiole width and length, leaf number per shoot, and final shoot height were correlated with SFB. The physiological traits that were also influential factors of shoot biomass were the leaf δ(13)C, the total nitrogen concentration, and the water content. Among the studied leaf traits, LA(max), leaf δ(13)C, and concentrations of chlorophyll a and b were identified as the most representative predictor variables for SFB, accounting for 73% of the variability in SFB. In conclusion, a combination of LA(max), leaf δ(13)C, and chlorophyll should be considered in selection programs for high-yield mulberry cultivars.